Curriculum Innovation in Practice: Strategies of Mathematics Teachers for Implementing Independent Learning in Indonesian Schools - Rahmayani, Sitti (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
The implementation of the Independent Learning Curriculum in Indonesia presents both challenges and opportunities for teachers to create more interactive, innovative, and relevant learning experiences aligned with 21st-century needs. This study explores the managerial strategies of mathematics teachers in implementing the Independent Learning Curriculum at UPT SMA Negeri 5 Pinrang, Indonesia. Using a qualitative descriptive method, data were collected through observations, in-depth interviews with four mathematics teachers selected through purposive sampling, and document analysis. The findings reveal that teachers adopted various innovative strategies, including interactive approaches, technology integration, humor in teaching, project-based learning, and diverse assessment methods to enhance student engagement. A formative assessment approach, with constructive feedback and appreciation for students' efforts, contributed to a supportive and productive learning environment. However, teachers also faced several challenges, including resource limitations, student motivation issues, and difficulties in implementing fair assessments. This study highlights the importance of combining technology, creativity, and pedagogical strategies to enhance the effectiveness of mathematics learning. These findings contribute to discussions on curriculum reform and offer practical implications for broader adoption within Indonesia’s education system.